A boronate-affinity magnetic molecularly imprinted polymer for luteolin recognition. Issue 7 (23rd January 2023) - Ding, Li-xin; Wang, Yong-qiang; Sun, Xue; Jiang, Zhao-qi; Wang, Xiao-yu; Zhou, Yan-fen; Hou, Xing-yu
Abstract : A novel boronate-affinity molecularly imprinted solid-phase extraction adsorbent is reported for the selective enrichment of luteolin. Abstract : In this study, 3-carboxyphenylboronic acid (CP)-functionalized amino-modified Fe3 O4 (Fe3 O4 @NH2 -CP, FNC) magnetic molecularly imprinted polymers (FNC@MIPs) were synthesized and applied for the quick identification and selective separation of luteolin (LTL). The structure and morphology were characterized in detail by Fourier transform-infrared spectroscopy (FT-IR), scanning electron microscopy (SEM), dynamic light scattering (DLS), X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD), thermogravimetric analysis (TGA), and vibrating specimen magnetometry (VSM) methods. The FNC@MIPs had a homogeneous shape, excellent magnetic characteristics, quick binding kinetics, a high adsorption capacity, acceptable selectivity, and stable reusability. The solid-phase extraction parameters and preparation conditions were both optimized. Under optimized conditions, the maximal adsorption capacity was 14.26 mg g −1 and the imprinting factor was 3.62. Furthermore, the experimental kinetics data were best fitted with the pseudo-first-order model ( R 2 = 0.9877), and the Langmuir model could describe the adsorption process ( R 2 = 0.9979), suggesting a monolayer covering. The practical application of the sorbent for LTL detection in Lonicera japonica Thunb samples showed recoveries in the range of 84.5–108.7%. Therefore, the strategy offers a fresh avenue for the extraction and purification of LTL.